A developmental perspective of the public library system as a service to the disadvantaged black communities of the Western Cape with special reference to the Cape Peninsula - Lawrence, G. N.(Graham Norman) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.P.A.) -- University of Stellenbosch, 1994.